PENINGKATAN KEMAHIRAN GURU MELALUI KOLABORATIF BLENDED LEARNING MENUJU REVOLUSI INDUSTRI 4.0 DI SMPN 271 JAKARTA - Rayung Wulan; Ardhi Dinullah Baihaqie; Suranto Saputra (Jurnal PkM Pengabdian kepada Masyarakat, 2022)
The industrial revolution 4.0 and the Covid-19 endemic have an impact on the world of education, one of which is the collaboration between cyber technology and automation technology. Learning media in the industrial revolution 4.0 era is getting to the highest level, which is currently running in the form of collaborative blended learning. However, the implementation of blended learning still requires compatibility, especially between the government and the school. Teachers and students are required to align their abilities according to the current era. The problem faced by SMPN 271, especially for elderly teachers, is that it is still difficult to make questions according to the semester learning plan by using the googleform, mentimeter software application. The purpose of community service activities at SMPN 271 is to improve the skills of teachers through collaborative blended learning towards the industrial revolution 4.0 at SMPN 271. The results obtained from the activity are that the school is able to understand and think positively about the development of the industrial revolution 4.0 and the school that originally do not understand to be familiar with the blended learning model, so that teachers and students are not bored in the learning process.